Dirâsah At-Tafkîr Al-Lughawi, At-Tarkîbi Lin-Nuchât Al-‘Arab - Syafi’i, Ahmad Helwani (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
This paper discusses the problem of kalâm, kalimah, tarkîb, and jumlah according to Arabic grammar, beginning with the meaning of jumlah, the difference of opinion of the scientists and Arabic grammarians, and how the correlation between kalâm and jumlah. In addition, this paper also contains parts of jumlah in Arabic and describes how the previous scientists’ view on the arrangement in the Arabic grammar rules are accompanied by syâhid in the form of Qur'anic verses.